Upland rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Mr. Bojang, Head of The Gambia?s Agricultural Communication Unit, encourages upland rice farmers to take advantage of animal traction, as a cost effective way of controlling weeds and carrying out other field operations.